Enhancing Teaching Skills Through Electronic Resources: A Study with Prospective Primary Teachers - Zhankushkov, Bauyrzhan; Amirova, Amina; Bakhtiyarova, Gulshat; Zhussupbekova, Gulsara; Nurgaliyeva, Saniya (Journal of Technical Education and Training, 2026)
The growing recognition of the potential of electronic resources to support pedagogy in teacher education highlights the importance of empirical research, particularly within developing educational systems such as Kazakhstan. This study examines the association between the use of electronic resources and teaching skills, reflective practices, and classroom management competencies among prospective primary school teachers. A quasi-experimental pre-post-test design was employed with a sample of 154 pre-service teachers from two Kazakhstani universities. The findings indicate that participants who used electronic resources demonstrated higher post-test scores in instructional planning and used more adaptive classroom management strategies than those receiving traditional instruction. These results suggest that digital tools may support the development of core competencies in teacher preparation, particularly in under-researched educational contexts. However, the use of non-equivalent groups drawn from different institutions represents a key limitation and warrants cautious interpretation of the findings. The study offers practical recommendations for curriculum developers aiming to integrate traditional and digital pedagogical approaches.